From information mismanagement to misinformation – the dark side of information management. Issue 1 (23rd November 2018) - Stone, Merlin; Aravopoulou, Eleni; Evans, Geraint; Aldhaen, Esra; Parnell, Brett David
Abstract : Purpose: This paper reviews the literature on information mismanagement and constructs a typology of misinformation that can be applied to analyse project planning and strategic planning processes to reduce the chances of failure that results from information mismanagement. This paper aims to summarize the research on information mismanagement and provide guidance to managers concerning how to minimize the negative consequences of information mismanagement and to academics concerning how to research and analyse case studies that might involve information mismanagement. Design/methodology/approach: Literature review accompanied by conceptual analysis. Findings: Information mismanagement is widespread in organizations, so all those involved in managing and researching them need to be far more aware of the damage that can be done by it. Research limitations/implications: The research is based on the Western society (Europe and North America). The same research should be carried out in other parts of the world. Also, all the case studies could usefully be investigated in more depth to apply the taxonomy. Practical implications: Managers should be much more aware of their own and others' tendencies to mismanage information to their own benefit. Social implications: Stakeholders in public sector activities, including citizens, should be much more aware of the tendency of the government and the public sector to mismanage information to justify particular policy approaches and to disguise failure. Originality/value: The taxonomy on information mismanagement is original, as is its application to project planning and strategic decision-making.